2013
DOI: 10.1111/ahg.12017
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mutation in FGD4/FRABIN Causes Charcot Marie Tooth Disease Type 4H in Patients from a Consanguineous Tunisian Family

Abstract: SummaryCharcot-Marie-Tooth (CMT) disease constitutes a clinically and genetically heterogeneous group of hereditary neuropathies characterized by progressive muscular and sensory loss in the distal extremities with chronic distal weakness, deformation of the feet, and loss of deep tendon reflexes. CMT4H is an autosomal recessive demyelinating subtype of CMT, due to mutations in FGD4/FRABIN, for which nine mutations are described to date. In this study, we describe three patients from a consanguineous Tunisian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 23 publications
(53 reference statements)
5
22
0
Order By: Relevance
“…Although the effects of CMT4H-linked Frabin mutations on ErbB receptor trafficking have not been examined, a number of disease-causing Frabin mutations were found in its phosphoinositide-recognition domains, namely, the two PH domains with binding specificity to PI(3,4,5)P 3 , PI(4,5)P 2 , and PI(3,4)P 2 and one FYVE domain with binding specificity to PI(3)P [72, 117119]. As described earlier, these phosphoinositides play important roles in regulation of ErbB2/ErbB3 receptor trafficking and signaling (Figs.…”
Section: Impaired Phosphoinositide-mediated Regulation Of Erbb Receptmentioning
confidence: 99%
“…Although the effects of CMT4H-linked Frabin mutations on ErbB receptor trafficking have not been examined, a number of disease-causing Frabin mutations were found in its phosphoinositide-recognition domains, namely, the two PH domains with binding specificity to PI(3,4,5)P 3 , PI(4,5)P 2 , and PI(3,4)P 2 and one FYVE domain with binding specificity to PI(3)P [72, 117119]. As described earlier, these phosphoinositides play important roles in regulation of ErbB2/ErbB3 receptor trafficking and signaling (Figs.…”
Section: Impaired Phosphoinositide-mediated Regulation Of Erbb Receptmentioning
confidence: 99%
“…CMT4H is an autosomal recessive demyelinating subtype of Charcot-Marie-Tooth disease, that we have first described in 2005 (De Sandre-Giovannoli, Delague et al 2005) and for which we and others have described FGD4 as the gene causing the disease (Delague, Jacquier et al 2007, Stendel, Roos et al 2007. One distinctive feature of CMT4H is the presence, in the nerves of patients, of recurrent loops of myelin, called outfoldings (De Sandre-Giovannoli, Delague et al 2005, Stendel, Roos et al 2007, Fabrizi, Taioli et al 2009, Arai, Hayashi et al 2013, Boubaker, Hsairi-Guidara et al 2013) These rare myelination abnormalities, have also been reported in other autosomal recessive demyelinating subtypes of Charcot-Marie-Tooth, i.e. CMT4B1 (MIM 601382), CMT4B2 (MIM 604563), and CMT4F…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis is established by the presence of biallelic pathogenic variants in FGD4. More than 30 mutations are described to date in FGD4, most of them resulting in a loss of the protein or a nonfunctional truncated protein (Delague, Jacquier et al 2007, Baudot, Esteve et al 2012, Boubaker, Hsairi-Guidara et al 2013. FGD4 encodes FRABIN, a Guanine Exchange Factor (GEF), carrying a Dbl Homology domain responsible for GDP/GTP exchange on the small RhoGTPases and more particularly Cdc42 and Rac1 (Umikawa, Obaishi et al 1999, Ono, Nakanishi et al 2000.…”
Section: Introductionmentioning
confidence: 99%
“…So far, at least 22 CMT4H families with FGD4 gene mutations have been reported (4,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). According to a review of the previous CMT4H cases, it is clinically characterized by early onset and slow progression, and most cases started their symptoms before 5 years old, ranging from birth to 2 nd decade (4,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). The severity of distal muscle weakness, amyotrophy, and sensory involvement varies between affected individuals.…”
Section: Discussionmentioning
confidence: 99%